2019
DOI: 10.1111/acps.12997
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of altered regional brain glucose metabolism in borderline personality disorder and bipolar II disorder

Abstract: S, Malt UF. Patterns of altered regional brain glucose metabolism in borderline personality disorder and bipolar II disorder.Objective: The relationship between borderline personality disorder (BPD) and bipolar II disorder (BIP-II) is disputed but understudied. Here, we investigated brain glucose metabolism in these patient groups and healthy control subjects (HCs). Methods: Sixty-five subjects, 22 BPD (19 females), 22 BIP-II (17 females), and 21 HC (14 females), were examined using 2-deoxy-2[18F]-fluoro-dgluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…As showed in Figure 1, seven studies were included into this meta‐analysis comprising 126 individuals with BD and 160 healthy controls (Altamura et al., 2017; Bauer et al., 2005; Boen et al., 2018; Brooks et al., 2008; Delvecchio et al., 2019; Li et al., 2012; Mah et al., 2007). Among these studies, all patients met the DSM‐VI criteria for BD type I or II.…”
Section: Resultsmentioning
confidence: 99%
“…As showed in Figure 1, seven studies were included into this meta‐analysis comprising 126 individuals with BD and 160 healthy controls (Altamura et al., 2017; Bauer et al., 2005; Boen et al., 2018; Brooks et al., 2008; Delvecchio et al., 2019; Li et al., 2012; Mah et al., 2007). Among these studies, all patients met the DSM‐VI criteria for BD type I or II.…”
Section: Resultsmentioning
confidence: 99%
“…For example, (Brooks, Hoblyn, & Ketter, 2010) and (Brooks, Hoblyn, Woodard, Rosen, & Ketter, 2009) reported significant hypometabolism in the prefrontal gyrus in BD while (Liu et al, 2012b) and (Xu et al, 2014a) reported increased activities in the prefrontal gyrus in BD. (Bøen, Hjørnevik, & Hummelen, 2019) reported hypometabolism in the striatum in BD. (Zhang et al, 2017) and (Zhang et al, 2020b) reported increased activities in the striatum in BD.…”
Section: Introductionmentioning
confidence: 99%
“…Several review articles summarized evidence in support of and opposition to the hypothesis that BPD belongs to the bipolar spectrum, with most of the recent reviews having concluded that BPD and bipolar disorder are valid and distinct diagnostic entities (Bassett et al, 2017; Bayes, Parker, & Fletcher, 2014; Ghaemi, Dalley, Catania, & Barroilhet, 2014; Magill, 2004; Paris, 2004; Paris & Black, 2015; Paris, Gunderson, & Weinberg, 2007; Parker, 2014, 2015; Smith, Muir, & Blackwood, 2004). A growing body of research that directly compares patients with BPD and bipolar disorder has demonstrated that patients with the two disorders differ in clinical characteristics (Mneimne, Fleeson, Arnold, & Furr, 2018; Richard-Lepouriel et al, 2019), frequency of suicide attempts (Bayes, Graham, Parker, & McCraw, 2018; Perroud et al, 2016; Richard-Lepouriel et al, 2019), neurobiological substrates (Boen et al, 2019; Das, Calhoun, & Malhi, 2014; Malhi et al, 2013; Radaelli et al, 2012; Rossi et al, 2012), neuropsychological profiles (Feliu-Soler et al, 2013; Gvirts et al, 2015), maladaptive self-schemas (Nilsson, Jorgensen, Straarup, & Licht, 2010), temperament (Eich et al, 2014), and history of childhood abuse and neglect (Bayes et al, 2018; Bayes et al, 2016b; Fletcher, Parker, Bayes, Paterson, & McClure, 2014; Mazer, Cleare, Young, & Juruena, 2019; Perroud et al, 2016; Richard-Lepouriel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%